Answer:
N2O(g) + 3 H2O(l) ---------------> 2 NH3(g) + 2 O2(g)
Explanation:
If we look at the reaction stated in the question, we will notice that the option chosen in the answer is the reverse of that reaction.
One thing is clear, if a reaction is possible, then its reverse reaction is equally possible. The equilibrium position may shift towards the forward or reverse reaction based on the conditions of the reaction.
Hence if the reaction, 2NH3(g) + 2O2(g) → N2O(g) + 3H2O(l) is possible, then the reaction, N2O(g) + 3 H2O(l) ---------------> 2 NH3(g) + 2 O2(g) is also possible.